Rechte und Verbindlichkeiten der Weiber - Pfizer, Benjamin Friedrich (Historische Quellen zur Frauenbewegung und Geschlechterproblematik ;, 1794)
The rights and responsibilities of a wife in the event of bankruptcy proceedings against her husband. Both general German law and the specifics of the laws in the state of Württemberg are explicated.